Molecular subtypes of gastrointestinal stromal tumors and their prognostic and therapeutic implications. (January 2017) - Szucs, Zoltan; Thway, Khin; Fisher, Cyril; Bulusu, Ramesh; Constantinidou, Anastasia; Benson, Charlotte; van der Graaf, Winette TA; Jones, Robin L
Gastrointestinal stromal tumors (GISTs) are composed of various molecular subtypes, with differing prognostic and predictive relevance. Previously, tumors lacking mutations in the KIT and PDGFRA genes have been designated as 'wild-type' GISTs; however, they represent a heterogeneous group currently undergoing further subclassification. Primary and secondary resistance to imatinib poses a significant clinical challenge, therefore ongoing research is trying to evaluate mechanisms to overcome resistance. Thorough understanding of the prognostic and predictive relevance of different genetic subtypes of GIST can guide clinical decision-making both in the adjuvant and the metastatic setting. Further work is required to identify tailored therapies for specific subgroups of GISTs wild-type for KIT and PDGFRA mutations and to identify predictive factors of resistance to currently approved systemic therapies.